Bundling Threats: Why Dominant Perceptions of China Changed in Europe - Breslin, Shaun; Mattlin, Mikael (Oxford University Press (OUP), 2025)
Popular perceptions of China in Europe have clearly shifted over the past few years. This article builds on the literature that assesses how narratives of China emerge and change, and how they influence policy on how best to respond to China's rise. We construct an analytical framework in which we identify two different types of reasons for change in dominant perceptions, underlying and precipitating, and a transmitting process (narrative diffusion). We argue that four underlying and three precipitating reasons together with active diffusion of a particular academic and policy narrative explain why dominant perceptions of China changed in Europe to predominantly negative within a relatively short time period. We explore what foundational assumptions this dominant narrative depends on, and what is considered as evidence (and evidence of what). We suggest that a projected threatening future image of China explains how current actions of Chinese actors are interpreted and that this interpretation in turn reinforces the projected future image in a circular logic, with clear policy implications. The associated assumptions, conflations, evaluation, and beliefs regarding ability and agency bundle together many different concerns that analytically should be kept separate. This leads to difficulties in discerning between diverse kinds of risks and threats on different timescales, with policymakers often opting for playing safe.